2012
DOI: 10.1097/ta.0b013e3182569849
|View full text |Cite
|
Sign up to set email alerts
|

Selective angiographic embolization of blunt splenic traumatic injuries in adults decreases failure rate of nonoperative management

Abstract: III, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 22 publications
3
58
1
1
Order By: Relevance
“…The spectrum of approaches has ranged in the literature from routine admission angiography for all patients with blunt splenic injury, 50 to the application of strictly defined selection criteria for angioembolization based on independent risk factors for failure. 53 All of these studies reported an extremely low failure rate for NOM, which is much lower than our base case of 20%.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…The spectrum of approaches has ranged in the literature from routine admission angiography for all patients with blunt splenic injury, 50 to the application of strictly defined selection criteria for angioembolization based on independent risk factors for failure. 53 All of these studies reported an extremely low failure rate for NOM, which is much lower than our base case of 20%.…”
mentioning
confidence: 67%
“…In recent reports, the probability of failure rates of NOM were reduced to below 10% for grade V injuries with the inclusion of angioembolization in the protocol for NOM. 53 In this type of situation, irrespective of the grade of the splenic injury, immediate splenectomy would never result in a better survival benefit than NOM, as the 2 strategies are equivalent only. Therefore, at institutions where the failure rate of NOM is below 20% irrespective of the grade of the splenic injury, all stable patients with blunt splenic injury and severe TBI should undergo a trial of NOM.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent retrospective review of 1,039 patients, of whom 19% underwent AE, found that the addition of AE to NOM significantly decreased the failure rate of this approach in patients with splenic injury Grades 4 to 5. 29 Although the reason(s) for this difference is obscure, it is conceivable that the significant comorbidities of LC, which have been shown to negatively affect outcome in surgical patients, 7,8,17,30,31 account for this disparity.…”
Section: Discussionmentioning
confidence: 99%
“…Indications to AE include CT evidence of ongoing bleeding with contrast extravasation outside or within the spleen and a concomitant drop in hemoglobin, tachycardia, and hemoperitoneum, as well as formation of pseudoaneurysm. The risk of failure after NOM is reasonably low (1-6 %) in low-grade injuries, and it can be improved with adjunctive angioembolization even in higher grades (0-9 %) [ 11 ]. However, rebleed and delayed spleen rupture are significantly more likely (38-55 % [ 3 , 12 ]) when highergrade injuries (grade IV-V) have been managed nonoperatively.…”
Section: Nonoperative Managementmentioning
confidence: 98%